On the participation of small-scale high performance combined heat and power plants to the Italian ancillary services market within Virtually Aggregated Mixed Units. (15th January 2022) - Bracco, Stefano; Bianchi, Enrico; Bianco, Giovanni; Giacchino, Alessandro; Ramaglia, Alessandro; Delfino, Federico
Abstract: The present paper derives from the need of determining new appealing mechanisms for the electrical system operators to encourage the participation of distributed energy resources to the markets of ancillary services. In particular, the research activity conducted by the University of Genoa and Ansaldo Energia company is focused on the small-scale cogeneration plants operating in the Italian Ancillary Services Market and evaluates the profitability of their inclusion within Virtually Aggregated Mixed Units. The developed methodology based on a technical and economic analysis is described and different scenarios are analyzed using as test case a typical installation of the 100 kW cogeneration microturbine produced by Ansaldo Energia. The affordability of choosing cogeneration technologies instead of traditional energy supply systems is critically investigated with the main goal of proposing and comparing some new innovative remuneration mechanisms for the services provided in the market by small-scale cogeneration units. The advantages for both the owner of the cogeneration plant and electrical system operators are described and the current legislative flaws are highlighted. Highlights: Participation of small-scale cogeneration units to the ancillary services market. Definition of new remuneration mechanisms. Comparative analysis of different operating scenarios.